Philosophy of Property as the Basic Premise of Propertology - A M Orekhov; M V Skachko (RUDN Journal of Philosophy, 2015)
Interdisciplinary character of contemporary social sciences leads to an idea of propertology - interdisciplinary teaching on property. Economics of property, sociology of property, law of property, political theory of property and others are among branches of propertology. Philosophy of property is to be considered as the first premise of propertology, setting methodological and theoretical basis for multifaceted research into this phenomenon. Structurally philosophy of property consists of the following sections: ontology of property, epistemology and methodology of research on property, axiology of property, ethics of a property-owner, - each of which forms its own area of investigation into property as complex system of social relations and attitudes.